The Effect of Local Wisdom-Based Materials on Students’ Reading Ability - Riryn Fatmawaty; Abdullah Farih; Riya Risqi Setyaningrum; Wahyu Hidayati Ningsih (ELITE JOURNAL, 2023)
The aim of this study to find out whether the material based on local wisdom has an effect on students' reading ability. The research design of this study is quasi-experimental research with a non-equivalent control group design. This study was conducted on students of class XI IPA SMAN 3 Lamongan, the sample used consisted of experimental and control classes each with 22 students, and the instruments used are test and non-test. The results of inferential statistical analysis using the paired sample t-test showed that the average value of the results of the experimental class's pretest reading ability was 67.77 while for the post-test experiment it was 85.55. In addition, the results of the questionnaire showed that there were about 89% of students gave a positive response, so it can be concluded that the application of material based on local wisdom has an effect on students' reading ability. Key Words: Local wisdom-based materials, reading ability